2022
DOI: 10.3390/d14050368
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Community of the Black Margate Anisotremus surinamensis (Teleostei: Haemulidae), from Coral Reefs off the Veracruz Coast, Mexico, Southern Gulf of Mexico

Abstract: We describe the composition and structure of the helminth community of the black margate Anisotremus surinamensis in coral reefs from the Parque Nacional Sistema Arrecifal Veracruzano (PNSAV) off the Veracruz coast. We examined a total of 78 specimens (total length TL range 21.7–77.9, mean 33.7 cm) (28 males, TL range 22.5–51.5, mean 32.7 cm; 50 females, TL range 21.7–77.9, mean 34.3 cm) of A. surinamensis. At least nine helminth taxa (seven intestinal) were found, for all of which A. surinamensis is a new hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Thus, in general, these component communities were characterized by a rather low diversity, but were well-ordered communities with a nested structure, as assessed by the NODF index ( Table 5 ). Stable parasite community structures, despite relatively low infection indices in fish hosts, have been also reported for other aquatic systems [ 35 , 111 , 112 , 113 ]. Moreover, similar results have recently been reported for two members of the family Sparidae ( Pagrus pagrus and Pagellus bogaraveo ) from the western Mediterranean Sea by Lablack et al [ 36 ], who found a homogeneous taxonomic composition of parasite communities for common taxa but not homogeneous for rare taxa (i.e., about the same as took place for Spicara smaris in the Crimean waters ( Figure 5 j)), suggesting a similar use of a common local pool of helminths.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, in general, these component communities were characterized by a rather low diversity, but were well-ordered communities with a nested structure, as assessed by the NODF index ( Table 5 ). Stable parasite community structures, despite relatively low infection indices in fish hosts, have been also reported for other aquatic systems [ 35 , 111 , 112 , 113 ]. Moreover, similar results have recently been reported for two members of the family Sparidae ( Pagrus pagrus and Pagellus bogaraveo ) from the western Mediterranean Sea by Lablack et al [ 36 ], who found a homogeneous taxonomic composition of parasite communities for common taxa but not homogeneous for rare taxa (i.e., about the same as took place for Spicara smaris in the Crimean waters ( Figure 5 j)), suggesting a similar use of a common local pool of helminths.…”
Section: Discussionmentioning
confidence: 64%
“…The processes responsible for parasite aggregation involve heterogeneity in the rates at which parasites are acquired or lost from the hosts. Parasite aggregation may result from uneven distributions of infective stages in time and space relative to hosts (i.e., spatial heterogeneity of parasite populations) [ 112 , 119 , 120 ] and genetic/acquired variation in susceptibility to infection arising from differences among hosts in immune resistance or behavior [ 121 , 122 ]. Some experimental studies have provided evidence that heterogeneity in exposure is more important than heterogeneity in susceptibility (i.e., individual susceptibility of hosts to parasites) [ 123 , 124 ].…”
Section: Discussionmentioning
confidence: 99%